RESIDENCIAL ATALAIA - HABITAÇÃO SOCIAL EM PRESIDENTE PRUDENTE - Sibila Corral de Area Leao Honda; Mayara Pissutti Albano (Universidade do Oeste Paulista, 2012)
This article seeks to discuss the social housing in medium-sized cities in Brazil, thinking on its implementation characteristics in urban structure and its residents. The study case is the city of Presidente Prudente, in São Paulo, state, taking one of the projects implemented with funding coming from the Federal program "Programa de Arrendamento Residencial (PAR)", the Residential Atalaia. The post-occupational survey.supports the analysis whose methodology was on-site survey. It is evident the neglect on the specific guidelines of the program, also fails to show directions of expansion and urban concentration. It reproduces the processes of implementation of social housing.